Stability of growth periods traits for soybean cultivars across multiple locations - Xiao-bo WANG; Zhang-xiong LIU; Chun-yan YANG; ran XU; Wei-guo LU; Li-feng ZHANG; Qian WANG; Su-hong WEI; Chun-ming YANG; Hui-cai WANG; Rui-zhen WANG; Rong ZHOU; et al. (Journal of Integrative Agriculture, 2016)
The growth periods (GPs, from planting/emergence to reproductive stage 8 (R8) of soybean cultivars vary in different ecological regions, especially in China with a very complex soybean cropping system. In this study, a 3-yr experimental study was undertaken in three geographical locations of China from 2008 to 2010, including the Northeast (40.66–45.85°N), Huang-Huai (34.75–38.04°N) and southern (22.82–30.60°N) eco-regions with about 250 accessions in each region to clarify the classification of maturity group (MG) and identify the cultivars with stable GP to increase the knowledge about the GP distribution of soybean cultivars in China. GPs of soybean cultivars in different eco-regions were significant different with a gradual decrease from 115–125 d in the Northeast part to the 85–100 d in the southern part of China. The geographical location was the major factor for GP of cultivars from the Northeast, while the year of planting was the major factor affecting the stability of GPs in Huang-Huai summer and southern summer soybean. AMMI2 (additive main effects and multiplicative interaction)-Biplot analysis showed that the GPs of soybean cultivars from the Northeast eco-region have a comparatively satisfactory environmental stability. Moreover, soybean cultivars with moderate GP/MG and stable environment adaptability in different eco-regions were identified based on the linear regression and AMMI analysis, which was important for the accurate classification of soybean MGs in future. Taken together, our results reflected the genetic diversity, geographical distribution and environmental stability of the Chinese soybean GP trait. Soybean cultivars with stable GP for various Chinese eco-regions would be beneficial for Chinese soybean genetic improvement, varietal introduction, exchange, and soybean breeding program for wide adaptability.